1963
DOI: 10.1037/h0044069
|View full text |Cite
|
Sign up to set email alerts
|

Counseling psychologists: Who are they?

Abstract: Division 17 members were studied on the basis of the 1961 Directory. Findings include: (a) Median age in 1962 was 48-49. 82% hold doctorates a half of which were conferred by about 10 institutions. Graduate work tends to be done in the same state as but in a different institution from the one of undergraduate study. More than half hold a job at colleges and universities, (b) 25% are ABEPP diplomates, 67% among Fellows and 12% among Members. More than 10% each are holding membership in Divisions 12, 5, 8, and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1965
1965
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…In general, the list here corresponds closely to that given by Clark (1957, p. 68) of the universities producing the largest numbers of Ph.D.'s in APA and also of universities producing and employing the largest numbers of significant contributors to psychology. The listing suggested by Table 1 is also quite similar to the one given by Yamamoto (1963) for the most-producing institutions for the APA Division of Counseling Psychology. Both overall and specific contributions of these selected schools is therefore well substantiated.…”
Section: Academic Degreesupporting
confidence: 57%
“…In general, the list here corresponds closely to that given by Clark (1957, p. 68) of the universities producing the largest numbers of Ph.D.'s in APA and also of universities producing and employing the largest numbers of significant contributors to psychology. The listing suggested by Table 1 is also quite similar to the one given by Yamamoto (1963) for the most-producing institutions for the APA Division of Counseling Psychology. Both overall and specific contributions of these selected schools is therefore well substantiated.…”
Section: Academic Degreesupporting
confidence: 57%
“…The data on the entire group also answer Gelso and Fretz's (2001) question concerning the percentage of counseling psychologists in full-time independent practice when counseling psychologists who do not belong to Division 17 are included in the analysis, that is, approximately 39%. During the 1940s, 1950s, and 1960s, approximately 5% of counseling psychologists in Division 17 worked primarily in private practice (Dreese, 1949;Samler, 1964;Yamamoto, 1963). This figure increased to 16% to 22% in the 1980s (Fitzgerald & Osipow, 1986;Watkins et al, 1986) with a similar figure observed for Division 17 members in the 1990s of about 20% (Gelso & Fretz, 2001).…”
Section: Employment Setting and Professional Work Activitiesmentioning
confidence: 74%
“…Dreese (1949) reported about 79% men and 21% women in 1949. Yamamoto (1963) found 84% men and 16% women in Division 17 based on the 1961 APA Directory. Fitzgerald and Osipow (1986) noted that the proportion of men and women in their sample of Division 17 members corresponded closely to the overall proportion in Division 17 at the time, about 80% men and 20% women.…”
Section: Demographic and Educational Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent national data (American Psychological Association, 2010;2009a) (Yamamoto, 1963) and 80% in the mid-1980's (Fitzgerald, & Osipow, 1986;Munley, Pate, & Duncan, 2008). In sum, these data stress the minimal presence of scholarship around the experiences of men in the field given the combined shifts in gender composition and proliferation of multiculturalism.…”
Section: The Place Of Men In Psychologymentioning
confidence: 97%